Multicomponent Solid Fuel Production Technology Using Waste Water - A. N. Pekhota; B. M. Khroustalev; Minh Phap Vu; V. N. Romaniuk; E. A. Pekhota; R. N. Vostrova; Thuy Nga Nguyen (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
An assessment is given to the problems of urban wastewater sludge utilization in our country and abroad, with determination of formation and usage level. Global trends in the reduction of carbon dioxide emissions exacerbate the urgency of solving the designated tasks. At the same time, recently, in connection with the EU’s plans to introduce a cross-border carbon levy, it has become necessary to reduce the carbon footprint from burning traditional fuels, which is an urgent problem of modern society. One of the directions that provide a solution to this problem is the replacement of part of the hydrocarbon fuel by the consumption of multicomponent solid fuel based on the use of combustible waste that is part of the multicomponent fuel. This solid fuel can be used to meet the needs of small consumers, for example, in the autumn-summer period to generate a drying agent for the preparation of grain on the threshing-floor, in small boiler houses, in sand drying plants of locomotive depots, heat installations of hangars and workshops, as well as in other heat-generating installations operating on solid fuels. At the same time, solving the problem of reducing the carbon footprint for Belarus is closely related to another urgent task – reducing the energy component of industrial products and the environmental consequences of storing accumulated and generated waste. The paper presents the results of joint scientific research in the field of application of modern technologies and equipment using electrohydraulic treatment to reduce and minimize the level of anthropogenic and polluting substances in wastewater sludge. The described technological equipment, technology and post-treatment modes reduce the content of harmful substances in the wastewater sludge composition even with short-term treatment. An assessment of the effectiveness of the developed technology for the use of sewage sludge is given, using the method of wet multicomponent briquetting to obtain a multicomponent fuel. The presented process flow diagram of multicomponent briquetting using sewage sludge and plant-wood waste directly shows the undeniable advantages of using watered wastewater sludge as a raw material for the production of solid fuel. At the same time, the optimally selected ratio of components and moisture content of the briquetted composition solves a number of technologically difficult problems that cannot be realized using traditional briquetting technologies. The presented data of the conducted research and the developed technology make it possible to expand the area of using wastewater sludge as a secondary renewable material resource.